Report on research, innovation and technological performance in Germany 2023 - EFI - Commission of Experts for Research; Innovation (Commission of Experts for Research and Innovation (EFI), 2023)
Core topics are: *Innovation in an ageing society *Markets for technology *German aerospace between old and new space - Further topics are: *R&I policy at a turning point in history *Creating agile governance structures *Tackling the grand societal challenges *Catching up and avoiding technological gaps *Removing barriers to innovation *Securing the skilled labour base *Key recommendations for action
Keywords: 330